Characterization of Megan Twohey Through Feminism Approach in She Said (2022) Movie - Febriani, Ni Made Intan; Juniartha, I Wayan (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study aims to examine the feminist approach employed in the characterization of Megan Twohey. The data were analyzed using a qualitative method. The data were gathered by using an observation method that was implemented into three approaches: watching the movie on Apple TV, reading the dialogues, and taking notes. The data were noted after watching and analyzing the film and reading the dialogues several times. By applying Murphy's characterization theory, the study identifies key traits such as bravery, intelligence, and unstoppable, which are crucial in depicting a strong, resilient female character. Additionally, using Tong's feminist theory, the research situates these traits within broader feminist discourses, highlighting how the character embodies various aspects of feminist ideologies, including the challenges faced by women in a male-dominated society. This analysis not only underscores the complexity of Megan Twohey's character but also contributes to a deeper understanding of how contemporary films can reflect and promote feminist values by portraying multifaceted female characters.